التصميم الانشائي لمبنى مدرسة ثانوية في مدينة الخليل - ادعيس, ابراهيم; حموري, اسلام; ناصر الدين, امير (جامعة بوليتكنك فلسطين - مباني, 2016)
The idea of this project is the structural design of a secondary school intended to be established in Hebron. This school composed of two different floors with a total area equals 4486 m2 , distributed over many rooms that serve students, teachers and any person visits this school. It also consists of Playground and cafeteria. The project design will provide optimal solutions for both sides of architectural and structural, so that it is taking into account the aesthetic , functional purposes and to provide comfort and ease and speed of use, the project will include the construction of the well-known elements of nodes, bridges, columns, foundations ... etc. The project will be designed based on ACI 318 - 14 code, will be used for several engineering programs, such as: AutoCAD 2015, Office 2013, ETABS 2015, SAFE 12, BEAMD, and we will refer to the references used, and in the end will be to provide detailed structural study, calculation and analysis of the loads design and construction plans for the units.
no of pages 94 , مباني 28/2016
Keywords: التصاميم الانشائية; ابنية المد